The impact of the training season on the body composition characteristics of the distance athletes in the high level athletes - bentahar, Ismail; ould ahmed, oualid (sports creativity, 2025)
The aim of the research is to study the body composition of Algerian athletes in enemy races in the competence of short races 400 m and 400 m hurdles where a scientific method has been followed in physical measurements. Athletes underwent several anthropometric measurements that allow determining the characteristics and indicators of the body composition of runners (weight, length, age , Muscle mass, adipose mass, and bone mass). As for the statistical community, it is represented in the high level hostilities participating in national, continental and Olympic championships, represented by the National Athletics Team and the Petroleum Club (GSP). The sample was represented by 12 runners, who were intentionally selected and surveyed Ml for the specialty of 400 m, as tools and devices were used for measurement, such as measuring skin folds and calculating the bone mass, and using the medical scale and measuring the body's circumference in addition to measuring length and taking the age of athletes for the senior category, up to several results, through the four training periods that make up the training season and comparison of composition Physical runners for the Algerian runners with elite runners in other countries, and the results were the absence of changes in the body composition through the training stages of the season and the profile of the Algerian runners with the Olympic elite runners in the race (400 m) -